A complex metal-organic framework catalyst for microwave-assisted radical polymerization. Issue 1 (December 2018) - Nguyen, Ha; Vu, Thanh; Nguyen, Dinh-Khoi; Trickett, Christopher; Doan, Tan; Diercks, Christian; Nguyen, Viet; Cordova, Kyle
Abstract Metal-organic frameworks (MOFs) have emerged as promising materials for use in practical applications of renewable energy, water harvesting, and catalytic transformation. Here we report the design of a highly porous MOF, termed MOF-907. Single crystal X-ray diffraction analysis, in combination with topological deconstruction, revealed a MOF based on trigonal prismatic secondary building units linked together by triangular and linear units to form a previously unseen net (nha ) with minimal transitivity, which is rational for these constituent building units. The catalytic properties of MOF-907 for the microwave-assisted radical polymerization of methyl methacrylate were demonstrated. MOF-907 produced a poly methyl methacrylate product in a short reaction time (30 min) with high yield (98%), high molecular weight (20, 680 g mol−1 ), and low polydispersity (1.23). Metal-organic frameworks are attractive candidates as catalyst materials. Here, the authors report a highly symmetric hierarchical framework with a rarenha net topology catalyzing microwave-assisted radical polymerization of methyl methacrylate in high yields.